2018
DOI: 10.3389/fpls.2018.00315
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Loci Conferring Reducing Sugar Accumulation and Conversion of Cold-Stored Potato Tubers Revealed by QTL Analysis in a Diploid Population

Abstract: Cold-induced sweetening (CIS) caused by reducing sugar (RS) accumulation during storage in low temperature in potato tubers is a critical factor influencing the quality of fried potato products. The reconditioning (REC) by arising storage temperature is a common measure to lower down RS. However, both CIS and REC are genotype-dependent and the genetic basis remains uncertain. In the present study, with a diploid potato population with broad genetic background, four reproducible QTL of CIS and two of REC were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…This finding is in agreement with the results of other studies, where measuring the expression of the genes involved in starch and sugar metabolism in tubers provided markers for AH but not for CS (Neilson et al 2017). Other studies have suggested that tendencies for the accumulation of reducing sugars after CS and RC are genetically independent, and reliable mapping of the QTLs allows dissection of the biological function of each QTL (Xiao et al 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with the results of other studies, where measuring the expression of the genes involved in starch and sugar metabolism in tubers provided markers for AH but not for CS (Neilson et al 2017). Other studies have suggested that tendencies for the accumulation of reducing sugars after CS and RC are genetically independent, and reliable mapping of the QTLs allows dissection of the biological function of each QTL (Xiao et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Mapping of quantitative trait loci (QTLs) has been performed in a number of experimental populations of diploid potatoes (Douches and Freyre 1994;Menendez et al 2002, Werij et al 2012Sołtys-Kalina et al 2015;Śliwka et al 2016;Braun et al 2017;Xiao et al 2018) in addition to a few association studies (Li et al 2008(Li et al , 2010Schreiber et al 2014). The genes involved in starch synthesis and degradation, the Calvin cycle and photorespiration, the glycolysis, oxidative pentose phosphate pathway, and the Krebs cycle are distributed across all twelve potato chromosomes (Chen et al 2001).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…41,61 The enzymatic darkening is associated with the availability/content of polyphenols 62 PPO and POD activity, 63 Coseteng & Lee, and presence of O2. PPO, present in almost all plant tissues, is composed of four copper atoms and a binding site for two aromatic compounds and O2, catalyzing the O-hydroxylation of O-monophenols in O-diphenols and yielding O-quinones 64 These o-quinones are polymerized with other quinones or phenolics, giving brown, black, brown or red pigments, called melanins, 65,66 as reported for beet, which also underwent darkening of the tissue during healing 23,41 due to the availability of phenolic compounds and increased PPO activity. In potato, the injury caused in the peeling and cutting stages of the sticks breaks the integrity of the membranes and causes the complete oxidation of the substrates by the PPO in the first 10 min after the cellular decompartmentalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, tubers stored at these temperatures show high sprouting and disease incidence (Wiberley-Bradford et al, 2016). Sprouts turn the tubers physically unsuitable for processing; in addition, the occurrence of sprouting may induce sweetening, resulting in a high sugar content, which is not adequate for processing (Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lower temperatures can be used to delay sprouting (Xiao et al, 2018). However, storage below 8 °C, may increase the darkening after frying, induced by the sweetening of the tubers (Duarte-Delgado et al, 2016).…”
Section: Introductionmentioning
confidence: 99%